The Experience of teaching computers course using Madrasati platform during the Corona pandemic from the teachers’ perspective - Al Ibrahim, Amal Abdullah (Journal of Curriculum and Teaching Methodology, 2023)
The current study aimed to explore the experience of computer teachers in distance teaching using Madrasati platform. The qualitative approach was used to achieve the purpose of the study, which used to understand the phenomenon in depth, the study uses a questionnaire with open questions. The data was collected and analyzed qualitatively using objective analysis. The number of participants was (15) female computer teachers. The results revealed that the teachers used all tools in the platform, and the study also showed a number of challenges that the teachers faced and how to overcome them, including the technical-psychological-educational- and practical challenges. The teachers showed a number of benefits they gain from using distance education, which was classified into students and teachers, and other educational gains. Finally, the study discussed the results of the research and the implication recommendations. The most important of which was the success of distance education, and that computer teachers were able to overcome obstacles and challenges. They also acquired a number of teaching and technical skills. The study came out with a number of recommendations, the most important of which are updating teacher preparation programs by adding online learning, as well as continuing to use Madrasati platform in blended learning.
Keywords: Distance education; learning management system; computer education; e-learning; Covid-19